Esoma. - Orendorff, Ryan Daniel. (Tufts Archival Research Center, 2005)
The Esoma Exercise System aims to shift cardiac rehabilitation to a patient-centered approach. Patients will play games powered by Microsoft Kinect and computer vision algorithms that recognize the execution of rehab exercises. Patients will wear physiological sensors while playing the games that monitor heart rate, blood oxygenation, etc. Rich feedback about their progress and improvement in physiological state will be embedded in the game to motivate self-efficacy. There will still be clinicians on the other side of the server, but they will act more as coaches that help patients make decisions for themselves based on the data. The system is being built as a CollaboRhythm plug-in so that it can benefit from the powerful tools for data visualization, communication, and social support.